Modern economic theory and the challenge of embedded tenure institutions: African attempts to reform local forest policies - Diaw, C. (Springer, 2005)
Cuatomary tenure, mingled with state law and occasional private titling, continue predominantly to govern African rural and forest lands. This is in spite of evolutionist theories that predicted its demise and colonial and post-colonial policies that tried actively to accelerate it. The chapter develops an anthropological conceptualization of the institutions of embedded tenure. With examples from Africa and various part of the world, the authors highlight the factors that account for the flexibility, adaptibility and resilience of this type of system. Embedded tenure has been able to cope with economic stress and hostile policies because of the unique way in which it nests private entitlements into the commons, and both of them into collective property and long-lasting social institutions. Two philosophical principles giving rise to three constitutional rights and four appropriations regimes make up its structure, while dynamic access and transformation rules govern the interlocking and transmutations of appropriation regimes across space and time. This opens three specific paths of agricultural change as well profuse right delegation and land transaction procedures. These have helped the system adapt to changing economic, demographic and social conditions since at least the 19th century. Reductionist economic analyses of non-market systems, includingn property rights, kinship, common property and non-wage systems contributed to relegating the most innovative aspects of these systems in the limbo of imperfect markets. More interested in "crafted" institutions, the CPR literature also failed to see or emphasize the theoritical and policy implications of the nesting of appropriation regimes in embedded tenure. Other analyses have tended to overemphasize the controversial role of traditional authority at the expense of a deeper institutional analysis of the embedded system. The chapter highlights the numerous policy mistakes that can derive from these forms of reductions. The authors conclude that to disentangle African forest policies from the social costs and inefficiencies of the past, it is necessary to integrate the complexity and validity of embedded tenure institutions and their demonstrated ability to adapt to legal pluralism and commodity markets.